Enterprise Breakups and Performance During the Transition from Plan to Market - Lizal, Lubomir; Singer, Miroslav; Svejnar, Jan (The Review of Economics and Statistics, 2001)
Using firm-level data, we estimate the effects of the major wave of 1991 breakups of Czechoslovak state-owned enterprises on the subsequent performance of the ‘master enterprises’ and spun-off divisions. We estimate the performance effects of spinoffs by comparing the performance of enterprises that remained intact throughout the 1990–1992 period to the performance of the master enterprises that experienced spinoffs and the newly spun-off subsidiaries. Our estimates suggest that the breakups had a significant immediate effect on the productive efficiency and on the profitability of industrial firms in 1991, and that the effect became much less significant in 1992. The effect is a negative function of the size of the spinoff, being positive for small to slightly above average-sized spinoffs and negative for very large ones. We cannot reject the hypothesis that the estimated effect was identical for the spun-off subsidiaries and the master enterprises that experienced the spinoffs. Our 1991 estimates suggest that the large firms created under the centrally planned system suffered from inefficiencies that were alleviated by the breakups. The 1992 estimates are consistent with increased competition and the appropriation of profits by managers.